Pentingnya Pengembangan Kompetensi Guru Terhadap Kualitas Pendidikan - Tasya Wislim; Yelfa Desica Jusman; Zefanya Fathiha Waldina (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The development of educational science accompanied by technological developments has brought about rapid evolution and competition in various groups such as in various aspects such as organizations or companies and even in the world of education itself. Meeting needs is also a challenge that requires human resources (HR) who are able to learn various technologies well, adapt easily, and respond to significant changes. Of course, in the world of education, teachers are educational personnel. Educators are important stakeholders in educational development and are the most influential factor in producing quality educational activities and results. Therefore, teachers must obtain sufficient education, training, development and experience to improve their qualifications in order to fulfill their duties and responsibilities. Responsibility is carried out with the help of skills that bring success, which determines the quality of education. Therefore, training and development is a basic need which is expected to influence increasing teacher competence and performance.